Bearing Capacity Analysis of Pile Foundations Using CPT and SPT Data: A Comparative Study of Meyerhof and Schmertmann Methods - Shubham Satyam; Subham Kumar Rai (Momentum International Journal of Civil Engineering (MIJCE), 2026)
Accurate estimation of pile foundation bearing capacity is essential for ensuring the safety, serviceability, and cost-effectiveness of geotechnical structures. Cone Penetration Test (CPT) and Standard Penetration Test (SPT) data are widely used for evaluating pile performance; however, differences among empirical prediction methods may lead to variations in design capacity. This study aims to compare the bearing capacity of single and group pile foundations estimated using the Meyerhof and Schmertmann methods based on CPT and SPT datasets. The analysis was conducted on reinforced concrete piles with a diameter of 0.80 m and an embedded depth of 16 m. Single-pile capacities were calculated using both methods, while group pile performance was evaluated using the Converse–Labarre efficiency approach. The results indicate that the Meyerhof method consistently produced higher allowable pile capacities than the Schmertmann method. For CPT-based analysis, allowable capacities ranged from 261.26 to 318.10 tons, whereas SPT-based analysis yielded capacities between 445.94 and 458.20 tons. Group pile capacities were estimated at 792.12 tons and 1352.09 tons based on CPT and SPT data, respectively. The findings suggest that the Meyerhof approach provides more conservative design flexibility for large-diameter piles. The study highlights the importance of selecting appropriate interpretation methods and integrating multiple site investigation techniques to improve the reliability of pile foundation design.